RECONCEPTUALIZATION OF THE INDEMNIFICATION FOR STATE FINANCIAL LOSS BY CORRUPTORS ON THE BASIS OF PROPORTIONALITY, EFFECTIVENESS, EFFICIENCY, AND FUTURE REACH - SUJANA DONANDI S (Association of Certified Fraud Examiners Indonesia Chapter, 2017)
ABSTRACTIn Indonesia, the concept of indemnification for state loss by corruptor has not met the elements of proportionality, effectiveness, efficiency, and future reach. Therefore, re-conceptualization of indemnification for state loss by corruptor is necessary to confront the cunning corruptor in hiding the proceeds of corruption. The re-conceptualization can be constructed by determining remedy sanction for every legal subject sentenced guilty to corruption. The remedy sanction should not only consider the amount of money corrupted, but also the time value of the money, the budget spent to handle the case, and the potential profits obtained when the money is used well as it should be. By this sanction, the amount of money determined as remedy sanction would be proportional and would not only cover as maximum as property acquired for the result of corruption as regulated by the current regulation. In addition, by this sanction, a civil lawsuit for the properties considered as the result of corruption that could spend much money and time would be no longer necessary. Someone convicted on corruption suppose to be automatically considered did default to his promise to the state. The default could be based on his failure in acting according to his official duty or based on an agreement in business relation between the legal subject and state. Should the corruptor couldn’t pay the remedy of state loss in full or partly, the remedy should not be replaced by prison sentence, but the remedy or the difference money should be reckoned as a debt to the state loss. Thus, the debt would be attached to the corruptor and would be a lifetime responsibility for the corruptor as long as he could not pay the debt to the state. The debt even would be continued by the heirs if the corruptor were pass away. Furthermore, this concept could reach the possibility that the wealth resulted of corruption would be used in the future because under these provisions, the future wealth gained by the corruptor could be executed as a part of the extinguishment of debt without considering whether the wealth were the result of corruption or not.